Intracardiac Visualization of Transcatheter Mitral Valve Repair in an In Vitro Passive Beating Heart. Issue 9 (1st September 2015) - Gelpi, Guido; Romagnoni, Claudia; Vismara, Riccardo; Mangini, Andrea; Contino, Monica; Gianfranco, Beniamino Fiore; Antona, Carlo
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.